Evaluation of the Mechanical Properties of Recycled Coarse Aggregate Concrete Against the Action of Fire - Andre Jhoel, Lamas Chavez (2024)
Growing concerns about sustainability and the search for greener alternatives in construction have led to a renewed interest in recycled concrete as a building material. Recycled concrete is produced using recycled aggregates, such as construction and demolition debris, instead of virgin aggregates, which reduces the demand for natural resources and the accumulation of waste. However, the viability of recycled concrete in high-temperature applications, such as fires or exposure to extremely high temperatures, has come under critical scrutiny. In this study we are going to talk about the differences between conventional concrete and concrete with recycled aggregate after being exposed to high temperatures, we will focus on issues of resistance to compression, traction and modulus of elasticity. We were able to obtain in our tests that the greater the amount of recycled aggregate that we use in the concrete, the lower mechanical properties we obtain with respect to conventional concrete after being exposed to high temperatures, this is due to the adhered mortar that the recycled aggregate presents (in in our case 42% adhered mortar).